OPTIMALISASI PERAN GURU DAN ORANG TUA DI DESA TANGGUL KULON-JEMBER DALAM PENGGUNAAN MEDIA ONLINE PENUNJANG PEMBELAJARAN SISWA - Ziana Alviani; Agus Supriono (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2022)
The Covid-19 pandemic has had a major impact on the weakening of the Indonesian education sector, including the community such as school teachers and parents. Teachers and parents play an important role in contributing to Indonesian education. Educational problems such as student learning during this pandemic are less effective and less than optimal. Less effective learning is caused by constraints from school teachers and parents. School teachers during the pandemic only do learning using whatsapp and google classroom media. The obstacle from parents is that they cannot control their children in playing cellphones during a pandemic, as a result, children's interest in learning is decreasing. A lack of understanding of online media that can support student learning is also one of the causes of teachers and parents of students having difficulty dealing with the impact of the Covid-19 pandemic. Seeing these conditions, it is necessary to carry out a coaching and training activity to optimize the use of online media in supporting an effective and optimal student learning process during the current Covid-19 pandemic. Keywords: learning, online media, covid-19. ABSTRAK Pandemi Covid-19 memiliki dampak besar terhadap melemahnya sektor pendidikan Indonesia, tidak terkecuali pada masyarakat seperti guru sekolah dan orang tua siswa. Guru dan orang tua siswa sangat berperan penting dalam kontribusi terhadap pendidikan Indoneisa. Permasalahan pendidikan seperti pembelajaran siswa di masa pandemi ini kurang efektif dan kurang optimal. Pembelajaran yang kurang efektif tersebut diakibatkan karena kendala dari guru sekolah dan orang tua siswa. Guru sekolah saat pandemi hanya melakukan pembelajaran menggunakan media whatsapp dan google classroom. Kendala dari orang tua siswa yaitu tidak bisa mengontrol anaknya dalam bermain handphone, akibatnya minat anak untuk belajar semakin berkurang. Pemahaman yang kurang mengenai media online yang dapat menunjang pembelajaran siswa juga menjadi salah satu penyebab guru dan orang tua siswa cukup kesulitan menghadapi dampak dari pandemi Covid-19. Melihat kondisi tersebut maka perlu dilakukan kegiatan pembinaan dan pelatihan penggunaan media online dalam mendukung proses pembelajaran siswa saat pandemi Covid-19. Kata kunci: pembelajaran, media online, covid-19